Busana Apps (Budaya Khas Nusantara Applications): Disemination And Culture Education of Indonesia Through the Puzzle Game in the Middle of Pandemic Covid-19 - Hamdani Hamdani; Billy Nugraha (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
Indonesian culture is very diverse, from Sabang to Merauke. Many people don't know about Indonesian culture. This is because they are rarely introduced to the knowledge of arts and culture. In its implementation, efforts to preserve culture experience challenges from the incoming foreign culture. Technological advances have an impact on society, one of which is the proliferation of various kinds of games. The image of games in society is still seen as an entertaining medium rather than a learning medium. The nature of games is challenging, addictive, and fun for those who like games. Technological developments also affect people's habits. One of them is smartphones. So a combination is needed by following the development of science and technology today. Busana Apps (Budaya Khas Nusantara Applications) is an application that displays a variety of cultures in Indonesia, from dance, music, and fine arts. This application is expected to help the interest of the community, especially children, to get to know the arts and culture in Indonesia, which is a legacy from their ancestors so that they can be maintained, cared for, and preserved properly. The results offered in this application are in the form of a puzzle game, which is an interactive game that can stimulate children's thinking patterns. Even with the Covid-19 pandemic like this, that cannot make people visit art venues directly. However, with this application, the public can get to know more about the arts in Indonesia.Keywords: Busana Apps, Game Puzzle, Covid-19 Pandemic. AbstrakBudaya Indonesia sangat beragam, dari Sabang sampai Merauke. Banyak orang yang belum tahu tentang budaya Indonesia. Hal ini dikarenakan mereka jarang dikenalkan dengan ilmu seni dan budaya. Dalam pelaksanaannya, upaya pelestarian budaya mengalami tantangan dari budaya asing yang masuk. Kemajuan teknologi berdampak pada masyarakat, salah satunya dengan menjamurnya berbagai jenis permainan. Citra game di masyarakat masih dipandang sebagai media hiburan daripada media pembelajaran. Sifat permainan yang menantang, membuat ketagihan dan menyenangkan bagi mereka yang menyukai permainan. Perkembangan teknologi juga mempengaruhi kebiasaan masyarakat. Salah satunya adalah smartphone. Sehingga dibutuhkan kombinasi dengan mengikuti perkembangan IPTEK saat ini. Busana Apps (Aplikasi Budaya Khas Nusantara) merupakan aplikasi yang menampilkan ragam budaya yang ada di Indonesia, mulai dari seni tari, musik dan seni rupa. Aplikasi ini diharapkan dapat membantu minat masyarakat khususnya anak-anak untuk lebih mengenal seni dan budaya yang ada di Indonesia yang merupakan peninggalan nenek moyang sehingga dapat dijaga, dirawat dan dilestarikan dengan baik. Hasil yang ditawarkan dalam aplikasi ini berupa permainan puzzle yaitu permainan interaktif yang dapat merangsang pola berpikir anak. Bahkan dengan pandemi Covid-19 seperti ini, tidak bisa membuat orang mengunjungi tempat seni secara langsung. Namun dengan adanya aplikasi ini masyarakat bisa lebih mengenal seni yang ada di Indonesia.Kata kunci: Busana Apps, Game Puzzle, Covid-19 Pandemic